A Study on The Impact of Paper Leaks on Students - Kamraju, M. (Universitas Pendidikan Indonesia (UPI), 2023)
This research study examines the impact of paper leaks on students in India. The study explores the causes and effects of paper leaks, legal and ethical implications, and prevention measures. The research design involves a quantitative approach with a survey as the data collection method. The sample size includes 500 students from various academic levels and institutions. The results indicate that paper leaks have a significant negative impact on student's academic performance, psychological well-being, and trust in the education system. The study highlights the need for stricter security measures, increased vigilance, and penalties for those involved in paper leaks.